(untitled) (Iranian Journal of Kidney Diseases, 2019)
Systemic lupus erythematosus (SLE) in children is associated with renal involvement in a majority. While glomerular involvement is a common manifestation, tubular involvement is rare. Tubular dysfunctions previously described with SLE are renal tubular acidosis (Type 1 and less commonly type 4). Isolated renal tubular acidosis without glomerular involvement has not been reported in childhood SLE. We report an adolescent girl with SLE, autoimmune thyroiditis and distal RTA who subsequently developed autoimmune hemolytic anemia. During a follow up of almost 7 years the girl never developed any proteinuria while the RTA persisted. Also during this period her mother was also diagnosed with SLE manifesting as thrombocytopenia.